Development of the East Coast of Tarakan as a Tourism Potential (Case Study: Tanjung Pasir) - Eko Prihartanto; Edy Utomo; Iif Ahmad Syarif (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
In orderTanjung Pasir is a coastal area located in the Mamburungan village, which is located at the very end of East Tarakan. In the Tanjung Pasir area, there are RT, one of which is RT 18. In this area most of the people make a living as fishermen and seaweed. Responding to this, researchers are interested in seeing the potential of the coast of the sand dune and how the forms of tourism management exist in the sand dune. In this study used qualitative research methods using a qualitative descriptive approach (Qualitative Descriptive). The location of this research is in the Mamburungan Village, Tanjung Pasir Village, Tarakan Timur District, Tarakan City, the survey was conducted several times, namely interviews in November and December 2019. The data collection stage used was that there were several techniques, namely Observation, Interview, Documentation, and Field Notes. . The data obtained are primary data, namely the results of direct interviews and the distribution of questionnaires to the community around the coastal area of Tanjung Pasir. In addition to primary data, there is also secondary data obtained from the internet and other sources. In this study, validation and rehabilitation were also tested. The results show that the potential of the ecosystem in the Tanjung Pasir area is very good and the sea conditions are also strategic for fishermen to be used as a place of livelihood by some local residents. The potential for tourism development is very good if done.